Mutations in sdh genes in field isolates of Zymoseptoria tritici and impact on the sensitivity to various succinate dehydrogenase inhibitors. (8th June 2017) - Rehfus, A.; Strobel, D.; Bryson, R.; Stammler, G.
Abstract : Zymoseptoria tritici is the causal agent of septoria tritici blotch (STB), a foliar wheat disease important worldwide. Succinate dehydrogenase inhibitors (SDHIs) have been used in cereals for effective control of STB for several years, but resistance towards SDHIs has been reported in several phytopathogenic fungi. Resistance mechanisms are target‐site mutations in the genes coding for subunits B, C and D of the succinate dehydrogenase (SDH) enzyme. Previous monitoring data in Europe indicated the presence of single isolates of Z. tritici with reduced SDHI sensitivity. These isolates carried mutations leading to amino acid exchanges: C‐T79N, C‐W80S in 2012; C‐N86S in 2013; B‐N225T and C‐T79N in 2014; and C‐V166M, B‐T268I, C‐N86S, C‐T79N and C‐H152R in 2015. The current study provides results from microtitre and greenhouse experiments to give an insight into the impact of different mutations in field isolates on various SDHIs. In microtitre tests, the highest EC50 values for all tested SDHIs were obtained with mutants carrying C‐H152R. Curative greenhouse tests with various SDHIs confirmed the findings of microtitre tests that isolates with C‐H152R are, in general, controlled with lower efficacy than isolates carrying B‐T268I, C‐T79N and C‐N86S. SDHI‐resistant isolates of Z. tritici found in the field were shown to have cross‐resistance towards all SDHIs tested. So far, SDHI‐resistant isolates of Z. tritici have been found in low frequencies in Europe. Therefore, FRAC recommendations for resistance management in cereals, including a limited number of applications, alternation and combination with other MOAs, should be followed to prolong SDHI field efficacy.